Does Congruence Between Brand Name and Brand Logo Influence Brand Affection?: An Experimental Study - Yaran Ögel, İlkin (Journal of Applied And Theoretical Social Sciences, 2022)
Undoubtedly, design and selection of the proper brand elements have a crucial role in the long-term success of a brand. Therefore, to establish strong and favorable brand meaning prior to market entry and enhance the acceptance of the new brand, an ultimate attention should be devoted to design and select brand elements that together convey consistent meaning. Herein, this study aims to examine the effect of interaction between sounds in brand names and shapes of brand logos on brand affection drawing upon sound and shape symbolism. To test the interaction effect between sound and shape, one experimental study was conducted. The findings of the study revealed that sounds in the brand names and shapes of the brand logos alone did not influence brand affection significantly. However, the results purported that the congruent combination of sounds in a brand name and shape of a brand logo significantly influenced brand affection compared to incongruent combinations. More specifically, the results indicated that when brand names are including high (low) frequency sounds and having angular (rounded) brand logo, brand affection towards the brand increased. These results are expected to both contribute to relevant literature and ensure applicable insights to the marketing practitioners who are responsible for designing and selecting brand elements.